“It's Kind of My Responsibility”: An Analysis of the Current EDI Discourse in Canadian STEM Fields and its Potential and Limitations to Contest Intersectional Discrimination - Fines-Neuschild, Mirjam; Tajmel, Tanja (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2024)
Since 2019, equity, diversity, and inclusion have become institutional priorities for Canadian funding agencies and universities under the acronym EDI. Here, we examine for the fields of science, technology, engineering, and mathematics (STEM) how the current EDI discourse unfolds in scientists’ understandings as EDI construct. This study presents data collected through 18 online interviews with researchers in STEM fields across Canada. For our analysis we apply critical discourse analysis and the matrix of domination. Four themes emerge from our data regarding STEM researchers’ understanding of and experience with the EDI construct: (a) EDI as trainable knowledge, (b) EDI as human resources/managerial issue, (c) EDI as assessable performance, and (d) EDI as individual initiative/lonely endeavour. Our findings suggest that the EDI discourse increases the awareness of the underrepresentation of groups in STEM fields. However, most interview participants demonstrate an essentialist understanding of identity decontextualized from institutional and structural processes of difference making along axes of gender, race, class, and body, amongst others. This critical discourse-analytical work contributes to an intersectional, power-acknowledging understanding of EDI in Canadian higher education.